2022
DOI: 10.3389/fpsyg.2022.1036848
|View full text |Cite
|
Sign up to set email alerts
|

The cuter, the better? The impact of cuteness on intention to purchase AI voice assistants: A moderated serial-mediation model

Abstract: Due to the lockdown, more and more people are used to communicating with AI voice assistants during the post-COVID era. This study investigates the relationship between the perceived cuteness of AI voice assistants and the intention to purchase via a moderated serial-mediation model. We tested a PLS-SEM model with 284 survey data from an online experiment. The findings indicate that: (1) different cuteness appearances lead to different levels of perceived cuteness; (2) perceived cuteness positively affects int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Moreover, while 28.09% of the articles did not explicitly use a guiding theory, the remaining 71.91% did. The most common theories include stimulus‐organism‐response theory (14 articles; e.g., Asante et al, 2023; Gao et al, 2022), the Technology Acceptance Model (6 articles; e.g., Moriuchi, 2019; Xiao & Kumar, 2021), and social presence theory (3 articles; e.g., McLean et al, 2021; Yu et al, 2022). Overall, our review uncovered AI‐based CE authors' adoption of 56 different theories.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, while 28.09% of the articles did not explicitly use a guiding theory, the remaining 71.91% did. The most common theories include stimulus‐organism‐response theory (14 articles; e.g., Asante et al, 2023; Gao et al, 2022), the Technology Acceptance Model (6 articles; e.g., Moriuchi, 2019; Xiao & Kumar, 2021), and social presence theory (3 articles; e.g., McLean et al, 2021; Yu et al, 2022). Overall, our review uncovered AI‐based CE authors' adoption of 56 different theories.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of VAs, it is defined as the extent to which technology makes individuals feel that they are interacting with another social entity (Pitardi & Marriott, 2021). This is especially true when technology can mimic human motivations, appearance, and behavior (Yu et al, 2022). AI agents that support interactive and reciprocal conversations can provide consumers with social cues that prompt a sense of social presence in their minds, increasing their willingness to interact with them (Guha et al, 2023).…”
Section: Social Presencementioning
confidence: 99%
“…AI agents that support interactive and reciprocal conversations can provide consumers with social cues that prompt a sense of social presence in their minds, increasing their willingness to interact with them (Guha et al, 2023). Extant research shows that VAs elicit higher levels of social presence as they emulate human speech and verbally respond to consumers (Yu et al, 2022). The perceived social presence increases consumers' favorable responses to and willingness to engage with VAs (Ruiz-Equihua et al, 2023).…”
Section: Social Presencementioning
confidence: 99%
“…For example, cute objects influence people’s compliance behaviors (Bellfield et al ., 2011), task attention (Nittono et al ., 2012), indulgent consumption (Nenkov and Scott, 2014), recycling behaviors (Wang et al ., 2017), decisions relating to temporal focus (Li et al ., 2019), risk preferences (Li and Yan, 2021), brand attitude (Septianto and Paramita, 2021), brand engagement (Lee and Hsieh, 2019), responses to destination marketing (Su and Li, 2023; Ye et al ., 2023; Xu et al ., 2022), prosocial behavior (Yang et al ., 2022; Jang, 2022; Shin and Mattila, 2021) and reaction after brand transgressions (Septianto and Kwon, 2022). Recent research has found an impact of cuteness in new domains, including AI (Lv et al ., 2022), AI voice assistants (Yu et al ., 2022), social robot faces (Chen and Jia, 2023) and insect-based foods (Marquis et al ., 2023).…”
Section: Theoretical Backgroundmentioning
confidence: 99%